Global Population: History, Geopolitics, and Life on Earth - Alison Bashford (Columbia University Press, 2014)
Global Population seeks to explain and untangle the great knot of ideas, politics, and public discussion that constituted this world problem: inherited from the nineteenth century; announced in Geneva in 1927; watched warily by the league of nations; acted upon by imperial states, decolonizing states, and neocolonial states; and after World War ii, acknowledged by the early united nations (un). it was a phenomenon that came deeply to shape the very idea of â€œdevelopment,â€ the demographically defined three worlds, and for some, an aspirational â€œone world.â€ it is hardly surprising that so many experts from so many different disciplines and traditions turned to think about the great changes in population trends across time and space. but how was it comprehended and created? â€œPopulationâ€ is often taken to be a sexual and reproductive issue in the first instance. yet it was a spatial and economic issue too, a question of land cultivation and food production. More than that, the population question persistently raised territorial matters: colonization, migration, and ultimately sovereignty. and what was at stake? Commentators at the time would have said unequivocally: war and peace. density in relation to cultivable landâ€”the crowded and the empty parts of the planetâ€”was the problem of the era, linked to war, even causally many of them thought. it was the spatial context combined with the biological phenomenon of population growthâ€”rarely just the latterâ€”that created a sense of global crisis after World War i. This was a proposition that simultaneously held prospects for global division and for global singularity. The world population problem as formulated from the 1920s onward, then, was as much about geopolitics as it was about biopolitics. This book traces the twentieth-century story of how a geopolitical problem about sovereignty over land gradually morphed into a biopolitical solution, entailing sovereignty over oneâ€™s person. it does so through investigation of the creators and the keepers of population knowledge. Global Population is only partly about the experts on human reproduction and sexualityâ€”medical doctors, human physiologists, birth control lobbyists. and it is only partly about â€œdemography,â€ the discipline devoted to population that emerged over the early twentieth century. indeed, of the long list of distinguished participants at the first World Population Conference, only two called themselves â€œdemographers,â€ although they were perhaps not as idiosyncratic as the other outliers: two self-identified â€œExplorers,â€ plus a humble â€œauthor,â€ Wells.8 They were all outnumbered by those whose expertise lay with land, food, and territory: plant geneticists, agriculturalists, soil scientists, scholars of international law and international relations, geographers, and economists. 9 after all, those troubled by population growth and distribution were concerned with the fertility of soil as least as much as the fertility of women.